Secondary prevention in the clinical management of patients with cardiovascular diseases. Core components, standards and outcome measures for referral and delivery: A Policy Statement from the Cardiac Rehabilitation Section of the European Association for Cardiovascular Prevention & Rehabilitation. Endorsed by the Committee for Practice Guidelines of the European Society of Cardiology. (29th August 2020) - Piepoli, Massimo F; Corrà, Ugo; Adamopoulos, Stamatis; Benzer, Werner; Bjarnason-Wehrens, Birna; Cupples, Margaret; Dendale, Paul; Doherty, Patrick; Gaita, Dan; Höfer, Stefan; McGee, Hannah; Mendes, Miguel; et al.
Abstract: Despite major improvements in diagnostics and interventional therapies, cardiovascular diseases remain a major health care and socio-economic burden both in western and developing countries, in which this burden is increasing in close correlation to economic growth. Health authorities and the general population have started to recognize that the fight against these diseases can only be won if their burden is faced by increasing our investment on interventions in lifestyle changes and prevention. There is an overwhelming evidence of the efficacy of secondary prevention initiatives including cardiac rehabilitation in terms of reduction in morbidity and mortality. However, secondary prevention is still too poorly implemented in clinical practice, often only on selected populations and over a limited period of time. The development of systematic and full comprehensive preventive programmes is warranted, integrated in the organization of national health systems. Furthermore, systematic monitoring of the process of delivery and outcomes is a necessity. Cardiology and secondary prevention, including cardiac rehabilitation, have evolved almost independently of each other and although each makes a unique contribution it is now time to join forces under the banner of preventive cardiology and create a comprehensive model that optimizes long term outcomes for patients and reduces the future burden on health care services. These are the aims that the Cardiac Rehabilitation Section of the European Association for Cardiovascular Prevention & Rehabilitation has foreseen to promote secondary preventive cardiology in clinical practice.